Maternal Mortality among Tribal Women at a Tertiary Level of Care in Bastar, Chhattisgarh - Chauhan, Prabha (Glob J Health Sci, 2012)
OBJECTIVES: The primary objective of this study is to study Maternal Mortality as per Gravidity among Tribal women at a tertiary level of care in Bastar, Chhattisgarh, India. MATERIALS AND METHODS: This is a hospital based, retrospective, reproductive-age mortality study (RAMOS) of tribal women of Bastar region, Chhattisgarh, that were admitted and managed in Obstetrics and Gynecology Department Govt. Medical College, Jagdalpur, Bastar, Chhattisgarh, between July 2007 and October 2011. There were total 120 cases. RESULT: Results of the present study showed that among 120 deceased tribal women highest maternal mortality 65 cases (54.166%) was noted in Primigravida (Nullipara G1P0), second highest maternal mortality 44 cases (38.333%) was noted in 2(nd) to 4(th) Gravida (Multipara), 10 cases (8.333%) were in 6(th) and 7(th) Grand Multigravida (Grand Multipara), and 01 case (0.833%) was in 8(th) Great Grand Multigravida. Direct causes of maternal mortality were highest 46 cases (38.333%) due to hypertensive disorders of pregnancy. Among direct causes second highest 18 cases (14.999%) maternal mortality were due to Rupture Uterus, third highest 12 cases (09.999%) of Septicemia, 06 cases (04.999%) of obstructed labor, 06 (04.999%) of Hemorrhage, 02 cases (01.666%) of unsafe Abortion, 02 cases (01.666%) of Pulmonary Embolism and 01 case (0.833%) due to Aspiration. Indirect causes of maternal mortality maximum 15 cases (12.5%) of Malaria and 10 cases (08.333%) were due to Anemia and 02 cases (01.666%) were of Sickle cell Anemia. The result of the present study showed that in tertiary level of care of Bastar in the year 2007 – 2008, 2008 - 2009, 2009 – 2010 and 2010 - 2011 the total maternal deaths were 34 (n=34); 35 (n=35); 27 (n=27) and 26 (n=26) respectively. The Maternal Mortality Ratio was 1611.876; 1615.881; 1168.325 and 1000.769 Per 1, 00,000 live births in the year 2007- 2008; 2008 - 2009; 2009 – 2010 and 2010 - 2011 respectively. In the year 2007 - 2008, maternal mortality percentage among tribal women was 80.314%; in the year 2008-2009 was 85.714% and was 100% in the year 2009 – 2010 and 2010 – 2011. CONCLUSION: Discusses and/or relates this study’s results to the need for improvement in the maternal health of tribal women of Bastar. It has been discussed well in the conclusion section.